Analisis Semiotika Michael Riffaterre dalam Al-Qur’an Surah Qs. Al-Jumu’ah : 62 Ayat 5 (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
The semiotic approach is one of the new approaches to studying of the Qur'an. This study is very important, because it tries to study the semiotic approach to Surah Al-Jumu'ah verse 5 using Michael Riffaterre's semiotic theory analysis knife with the following steps: First, Heuristic and Hermeneutics reading. Second, Matrix, Model and Variant Analysis. Third, Intertextuality (Hypogram). Fourth, new meaning in the text. This study uses the method (library research) by reviewing relevant literature as the main data source. The analysis was carried out qualitatively through a literature review of books, books and scientific articles related to the object of study. This study draws the following conclusions: first, heuristic reading is found in linguistics or vocabulary according to the text and shows the indirectness of expression in some of its linguistic vocabulary. Second, the results of the second reading found its hermeneutic point in the sentence "Their parable is like a donkey carrying a thick book". Third, the matrix (is an implied message from the text: "don't be like a donkey carrying a thick book, but doesn't know what it is carrying". The model is found 3 times in the text, all three have related meanings, which are the actual form of the matrix. Variants are found in other texts, namely (hadith) narrated by Ibn Abbas. Fourth, Hypogram is included in the potential hypogram type, because the meaning is not directly obtained from the text but rather in the interpretation of the text.